Liposome engraftment and antigen combination potentiate the immune response towards conserved epitopes of the malaria vaccine candidate MSP2. Issue 12 (19th March 2021) - Das, Sreedam C.; Price, Jason D.; Gosling, Katharine; MacLennan, Nicola; Ataíde, Ricardo; Seow, Jeffrey; Irani, Vashti; Atmosukarto, Ines I.; Anders, Robin F.; Richards, Jack S.; MacRaild, Christopher A.; Norton, Raymond S.
Graphical abstract: Highlights: Liposome engraftment of MSP2 induces a strong immune response. Liposome engraftment induces antibodies directed towards conserved epitopes on MSP2. Antibodies raised against liposome-engrafted MSP2 can recognise native MSP2. Lipid-dependent antibodies fix complement. Abstract: Merozoite surface protein 2 (MSP2) is a highly abundant, GPI-anchored surface antigen on merozoites of the malaria parasite Plasmodium falciparum . It consists of highly conserved N- and C-terminal domains, and a central polymorphic region that allows all MSP2 alleles to be categorized into the 3D7 or FC27 family. Previously it has been shown that epitope accessibility differs between lipid-bound and lipid-free MSP2, suggesting that lipid interactions modulate the conformation and antigenicity in a way that may better mimic native MSP2 on the merozoite surface. Therefore, we have immunised mice with MSP2 engrafted onto liposomes using a C-terminal tether that mimics the native GPI anchor. To improve the immunogenicity of the formulated antigen, liposomes were supplemented with Pathogen Associated Molecular Pattern molecules, specifically agonists of the Toll-like receptor 4 (TLR4) or TLR2. Induced antibodies were directed mostly towards conserved epitopes, predominantly in the conserved C-terminal region of MSP2. We also found that immunisation with a combination of 3D7 and FC27 MSP2 enhanced antibody responses to conserved epitopes, and that the overall responses of mice immunised with MSP2-engrafted liposomes were comparable in magnitude to those of mice immunised with MSP2 formulated in Montanide ISA720. The antibodies elicited in mice by immunising with MSP2-engrafted liposomes recognised the native form of parasite MSP2 on western blots and were found to be cross-reactive with isolated 3D7 and FC27 merozoites when investigated by ELISA. The liposome-tethered MSP2 induced higher titres of complement-fixing antibodies to 3D7 and FC27 MSP2 than did MSP2 formulated in Montanide ISA720. Our results indicate that liposomal formulation represents a viable strategy for eliciting a strong immune response that favours conserved epitopes in MSP2 and thus a strain-transcendent immune response.